The halal economy as a strategic driver of sustainable agricultural development in Bulgaria - Petrov, Daniel (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2025)
The study examines the institutional and market readiness of Bulgarian agricultural producers to adopt halal certification within the framework of the Islamic moral economy and the European Union’s sustainability agenda. The growing global demand for halal products has positioned certification as a key driver of ethical and environmentally responsible production; however, in Bulgaria, the absence of a legal framework and national certification authority remains a significant barrier. The research employs a mixed-method approach, combining SWOT analysis of macroeconomic and institutional conditions with a quantitative survey of 126 agricultural holdings proportionally distributed across six NUTS-2 regions. The data were analyzed using Principal Component Analysis (PCA) to identify the underlying determinants of readiness. The results show strong market motivation and environmental compatibility but low institutional trust due to regulatory uncertainty. Three main factors—(1) institutional trust and awareness, (2) market motivation and orientation, and (3) sustainability and ethics—shape the readiness of producers to engage in halal certification. The findings indicate that while Bulgaria possesses favorable geographic, structural, and ecological advantages, the successful integration into the halal economy depends on coordinated institutional efforts, improved policy design, and enhanced stakeholder awareness. The study recommends establishing a national halal certification authority and integrating halal standards into sustainable agricultural programs to strengthen competitiveness and export potential.